Terminator vault the complete story behind the making of the Terminator and Terminator 2: Judgment day - Nathan, Ian (Aurum Pr., 2013)
Born out of James Cameron's fever dream, the relentless Terminator has become a cinematic juggernaut. The original ground-breaking film, The Terminator, and its mighty sequel, Terminator 2: Judgment Day, not only assured the blockbuster career of their director but also turned their star, Arnold Schwarzenegger, into an icon. Movies about the dark side of humanity's love affair with technology, they redefined the boundaries between science fiction, horror and action, and set astonishing new standards for special effects
Keywords: Terminator two - Judgement day; The Terminator; Terminator (Motion picture); Terminator 2 (Motion picture)